2006
DOI: 10.1039/b602961b
|View full text |Cite
|
Sign up to set email alerts
|

Pumpless, selective docking of yeast cells inside a microfluidic channel induced by receding meniscus

Abstract: We present a simple cell docking method induced by receding meniscus to capture non-adherent yeast cells onto microwells inside a microfluidic channel. Microwells were fabricated either by capillary moulding of UV curable polyurethane acrylate (PUA) onto glass substrate or direct replica moulding of poly(dimethyl siloxane) (PDMS). A cell suspension of the budding yeast, Saccharomyces cerevisiae, was introduced into the microfluidic channel by surface tension driven capillary flow and a receding meniscus was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 35 publications
0
72
0
Order By: Relevance
“…1(a). [29][30][31] A small amount of the PUA precursor (y0.1-0.5 mL) was dropdispensed on the substrate and a first-replicated PUA mould (same material but without active acrylate groups) was directly placed onto the surface. The PUA precursor spontaneously moved into the cavity of the mould by means of capillary action and was cured by exposure to UV for y20 s. After curing, the mould was peeled off from the substrate using a sharp tweezer.…”
Section: Fabrication Of Microfluidic Channel With Pua Nanopatterned Smentioning
confidence: 99%
“…1(a). [29][30][31] A small amount of the PUA precursor (y0.1-0.5 mL) was dropdispensed on the substrate and a first-replicated PUA mould (same material but without active acrylate groups) was directly placed onto the surface. The PUA precursor spontaneously moved into the cavity of the mould by means of capillary action and was cured by exposure to UV for y20 s. After curing, the mould was peeled off from the substrate using a sharp tweezer.…”
Section: Fabrication Of Microfluidic Channel With Pua Nanopatterned Smentioning
confidence: 99%
“…Systems composed of a multitude of micro-channels with open outlets can be used for parallel assays and enable high throughput microfluidics (Juncker et al 2002;Park et al 2006;Zimmermann et al 2007;Namasivayam et al 2003). On the other hand, the use of open outlets is the cause of side effects mostly related to evaporation and contamination.…”
Section: Introductionmentioning
confidence: 99%
“…To test whether the cells captured in the cell chip platform were capable of processing biological responses, they were treated with the mating pheromone (α-factor), and their mating responses were analyzed by monitoring the transcription of a well-known mating gene fus1. Stimulation of haploid yeast cells with the mating pheromone is known to initiate MAP kinase signaling responses (Park et al, 2006b;. By using a yeast strain carrying the fus1-EGFP reporter, we monitored and compared the mating responses of the captured, HU-treated, and bulk cells.…”
Section: Viability Of Captured Cellsmentioning
confidence: 99%
“…S. cerevisiae cells are known to differ in size and shape according to the phase of the cell cycle (Alberghina et al, 2003;Rupes, 2002). We have previously shown that yeast cells can be captured by using cell chips with microwells of different sizes and shapes (Park et al, 2006b;. Yeast cells are the smallest at the G1 phase and could be separated from the bulk population by capturing them in microwells with circular cavities of diameter 8 μm.…”
Section: Introductionmentioning
confidence: 99%